2018
DOI: 10.1016/j.compedu.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

How extroversion affects student attitude toward the combined use of a wiki and video recording of group presentations

Abstract: The aim of this paper is to analyze the effect of extroversion on students' attitude toward the combined use of a wiki and the video recording of oral presentations to improve communication skills using a quantitative approach. The model includes stress because it is considered an important aspect in public speaking situations, especially so in a case like ours where the videos will be available to the class. The students' enjoyment and the relative advantages of the learning activity are also included because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 74 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Extroverts find social situations more pleasant than introverts, and therefore are likely to enjoy breakout room interaction with peers more than the introverts. Previous research has found that extroverts are more willing to speak in public and that they experience lower levels of anxiety (Fraj-Andrés et al, 2018).…”
Section: Extroversionmentioning
confidence: 95%
“…Extroverts find social situations more pleasant than introverts, and therefore are likely to enjoy breakout room interaction with peers more than the introverts. Previous research has found that extroverts are more willing to speak in public and that they experience lower levels of anxiety (Fraj-Andrés et al, 2018).…”
Section: Extroversionmentioning
confidence: 95%
“…Furthermore, they are more likely to actively maintain social relationships (affiliation and attachment). Indeed, research has found that extroverts perceive reduced stress and greater enjoyment related to the use of ICTs (Fraj-Andrés et al, 2018). This led us to formulate the following hypothesis:…”
Section: The Impact Of Extroversionmentioning
confidence: 97%
“…IoT can associate with perceived attributes, a convenient manner to undertake the IoT service in comparison with the traditional way. Literature reveals that attitude towards behaviour was reported as one of the key constructs of innovative adoption associated with relative advantages (Fraj-Andrés et al, 2018). Thus, the following hypothesis has been constructed: H 3 : There is a significant relationship between relative advantage and attitude towards behaviour …”
Section: Research Design and Hypothesis Developmentmentioning
confidence: 99%